2000
DOI: 10.1001/archsurg.135.7.806
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Billroth I Gastrectomy Compared With Conventional Open Gastrectomy

Abstract: Background: Although several studies compare surgical results of laparoscopic and open colonic resections, there is no study of laparoscopic gastrectomy compared with open gastrectomy. Hypothesis: When compared with conventional open gastrectomy, laparoscopy-assisted Billroth I gastrectomy is less invasive in patients with early-stage gastric cancer. Design: Retrospective review of operative data, blood analyses, and postoperative clinical course after Billroth I gastrectomy. Setting: University hospital in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
260
3
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(285 citation statements)
references
References 25 publications
17
260
3
5
Order By: Relevance
“…A body temperature greater than 38 °C is one of the clinical manifestations of systemic infl ammatory response syndrome (SIRS) [26], and patients can suffer greatly from this complication. The change in body temperature was as we expected and was similar to the results of previous reports [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…A body temperature greater than 38 °C is one of the clinical manifestations of systemic infl ammatory response syndrome (SIRS) [26], and patients can suffer greatly from this complication. The change in body temperature was as we expected and was similar to the results of previous reports [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan and Korea, the superiority of laparoscopyassisted gastrectomy (LAG) for early gastric cancer compared with conventional open gastrectomy has been confirmed by both randomized and nonrandomized clinical studies, with advantages including less intraoperative bleeding, less pain, and shorter postoperative hospital stays [4][5][6][7][8][9][10][11][12]. Reported postoperative complication rates are comparable between LAG and conventional open gastrectomy cases.…”
Section: Introductionmentioning
confidence: 99%